Propos sur les sélaciens des côtes tunisiennes - CAPAPE, Christian (INSTM Bulletin : Marine and Freshwater Sciences, 1987)
The author presents a biogeographic study of the 59 species of selachians of the Tunisian coasts based on the classification of Quignard (1978) concerning the fishes of the Mediterranean. Some data about the occurrence, the abundance, the bathymetry and the habitat of the same species in the interior of the Tunisian marine area are also presented.